Thermoplastic elastomer composite polypropylene resin composition and preparation method thereof
By adding raw materials such as styrenic thermoplastic elastomer and scratch-resistant enhancer to polypropylene materials, a thermoplastic elastomer composite polypropylene resin composition is formed, which solves the problem that polypropylene materials are prone to scratches during use and improves Improve the impact resistance and interface repair performance of the material.
Patent Information
- Application Number
- CN202411290559.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polypropylene materials are prone to minor scratches or scratches during use, and cannot fundamentally eliminate scratches on the surface of the material.
It uses polypropylene and styrenic thermoplastic elastomer as the base material, and adds scratch-resistant enhancers, nano-silica, antioxidants, lubricants, heat stabilizers, dimethylhydroxy silicone oil, nano-graphene oxide and Nano-hydroxyapatite and other raw materials are used to form a thermoplastic elastomer composite polypropylene resin composition through reasonable proportions and preparation methods.
It improves the flexural modulus and impact resistance of the material, enhances the impact toughness of the material, and achieves reversible physical cross-linking through multiple hydrogen bonds, improving the interface repair performance and reducing scratches on the material surface.
Smart Images

Figure CN119331342A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polypropylene composites, and in particular to a thermoplastic elastomer composite polypropylene resin composition and a preparation method thereof. Background Art
[0002] Thermoplastic elastomer is a copolymer polymer or a variety of physically synthesized polymer materials that have the characteristics of high elasticity, high strength and high resilience of rubber and the characteristics of injection molding. As a new type of multifunctional environmentally friendly material, thermoplastic elastomer can replace some rubber products in use and has a very broad application market.
[0003] Polypropylene is a widely used general-purpose plastic that is easy to process and has better comprehensive properties than other plastics, but its poor impact resistance restricts its application. Blending polypropylene with thermoplastic elastomers can not only improve the transparency of the material but also improve the toughness of the material. The elastomer is distributed as a dispersed phase in the continuous phase of polypropylene. When subjected to external forces, the elastomer particles act as stress concentration points and deform preferentially under impact to consume energy.
[0004] The properties of plastic elastomers vary greatly depending on the degree of crosslinking of the elastomer, and show huge differences in use. Currently, styrene-based thermoplastic elastomers are commonly used for polypropylene modification. They have excellent stability, heat resistance, oxidation resistance and other properties, and the blending system is easy to obtain good performance, but slight scratches or scratches are inevitable during specific use. Currently, amides or silicones are often added to improve the smoothness of the material surface and reduce the brightness change at the scratches, but scratches on the material surface cannot be fundamentally eliminated. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a thermoplastic elastomer composite polypropylene resin composition and a preparation method thereof.
[0006] A thermoplastic elastomer composite polypropylene resin composition, the raw materials of which include, by mass, 100-150 parts of polypropylene, 10-30 parts of styrene-based thermoplastic elastomer, 0.1-1 part of nucleating agent, 3-9 parts of scratch resistance enhancer, 1-5 parts of nano silicon dioxide, 1-3 parts of antioxidant, 0.1-1 part of lubricant, 1-2 parts of heat stabilizer, 5-10 parts of dimethyl hydroxy silicone oil, 1-5 parts of nano graphene oxide and 5-10 parts of nano hydroxyapatite; wherein the scratch resistance enhancer adopts carboxyl polysiloxane as the main chain, and amino-terminated polyamidoamine is grafted on the carboxyl polysiloxane.
[0007] Preferably, the melt flow rate of the polypropylene is 15-20 g / 10 min at 230° C. and a load of 2.16 kg.
[0008] Preferably, the styrene-based thermoplastic elastomer is at least one of a styrene-butadiene block copolymer, a styrene-isoprene block copolymer, and a hydrogenated styrene-butadiene-styrene block copolymer.
[0009] Preferably, the nucleating agent is dicyclohexylterephthalamide or N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide.
[0010] Preferably, the scratch resistance enhancer is prepared by the following specific operation: adding carboxyl polysiloxane to ethyl acetate and stirring for 10-30 minutes, adding amino-terminated polyamidoamine thereto, ultrasonically treating for 10-20 minutes, adding N-hydroxysuccinimide and a catalyst, stirring at 80-90° C. for 1-4 hours, removing ethyl acetate by reduced pressure distillation, washing, and vacuum drying.
[0011] More preferably, the molecular weight of the carboxyl polysiloxane is 80,000-100,000.
[0012] More preferably, the mass ratio of carboxyl polysiloxane, amino-terminated polyamidoamine, N-hydroxysuccinimide and catalyst is 2-6: 1-2: 0.1-1: 0.001-0.1.
[0013] More preferably, the catalyst is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.
[0014] Preferably, the antioxidant is antioxidant 1010 or / and antioxidant 168.
[0015] Preferably, the heat stabilizer is at least one of an amine heat stabilizer and a phosphite heat stabilizer.
[0016] Preferably, the lubricant is at least one of a stearic acid complex ester lubricant and an amide lubricant.
[0017] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 30-50° C. for 1-3 min, add nano-hydroxyapatite thereto, continue stirring for 1-2 h, and perform ultrasonic treatment to obtain pretreated silicone oil; S2, mixing polypropylene, styrene-based thermoplastic elastomer, nucleating agent, pre-treated silicone oil, scratch resistance enhancer, nano silicon dioxide, antioxidant, lubricant, and heat stabilizer, melt-extruding, and granulating.
[0018] Preferably, in S1, the ultrasonic frequency is 10-20 kHz.
[0019] Preferably, in S2, a twin-screw extruder is used for melt extrusion, the aspect ratio of which is 20-25:1 and the melting temperature is 185-210°C.
[0020] Beneficial effects: The present invention adopts polypropylene and styrene thermoplastic elastomer as base materials and reasonably adjusts the proportions with other raw materials. Not only does it have a wide molding temperature range, but it can also be recycled and reused, thus having a high recycling value.
[0021] The present invention combines a lamellar graphene structure on the organic silicon macromolecular chain of dimethylhydroxy silicone oil, and then further forms a stable hydrogen bond structure with the hydroxyl group on the nano-hydroxyapatite. Since the graphene oxide is a honeycomb structure at the microscopic level, it is combined with the organic silicon macromolecular chain, so that the dispersion uniformity in the base material composed of polypropylene and styrene thermoplastic elastomer is extremely high, which promotes the excellent bending modulus and impact resistance of the obtained composition, and its stable lamellar structure can effectively protect the interface and enhance the impact toughness of the material. Even if the material is damaged, the organic silicon macromolecular chain cooperates with the nano-hydroxyapatite to repair and combine again through hydrogen bonds, and the repair performance is good.
[0022] The present invention uses carboxyl polysiloxane as the main chain, and combines it with terminal amino polyamide amine. By controlling the ratio of the two, the degree of grafting on the main chain of polysiloxane is controlled, so that the obtained scratch resistance enhancer has a similar main chain structure to the pretreated silicone oil, and the molecular chain structures are entangled with each other. It has been confirmed by experiments that the present application exhibits reversible thermoplasticity when heat-treated at a temperature of 40-50°C, and reversible physical cross-linking is achieved by using multiple hydrogen bonds therein, forming hydrogen bonds as physical cross-linking points, and excellent interface repair performance.
[0023] In the scratch resistance enhancer, since a large number of dendritic polyamide amine structures are combined on the silicone molecular chain and dispersed in the continuous phase polypropylene, when subjected to external force, its dendritic structure is similar to an anchoring structure and combined with polypropylene, which can not only quickly disperse the external force through the entangled silicone molecular chains, but also make the surface structure not easy to break, and the impact resistance is further enhanced.
[0024] The thermoplastic elastomer composite polypropylene resin composition obtained by the invention can be obtained by screw extrusion granulation, the preparation method is simple, the process conditions are easy to control, and it is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a comparison chart of the bending modulus and impact strength of the samples obtained by injection molding the thermoplastic elastomer-composite polypropylene resin composition obtained in Example 5 and Comparative Examples 1-2.
[0026] Figure 2It is a comparison chart of the tensile strength and elongation at break of the samples obtained by injection molding the thermoplastic elastomer-composite polypropylene resin composition obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 3 It is a comparison chart of the dL values of the samples obtained by injection molding the thermoplastic elastomer-composite polypropylene resin composition obtained in Example 5 and Comparative Examples 1-2.
[0028] Figure 4 It is a ΔL variation diagram of the samples obtained by injection molding the thermoplastic elastomer-composite polypropylene resin composition obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] The polypropylene used below was purchased from Suzhou Tianli Plastic Co., Ltd., and its melt flow rate was 18g / 10min at 230°C and a load of 2.16kg. The styrene-butadiene block copolymer used below was purchased from Shandong Moufeng Industry and Trade Co., Ltd., model YH-792E; the styrene-isoprene block copolymer used below was purchased from Dongguan Mourui New Materials Co., Ltd., model 1106; the hydrogenated styrene-butadiene-styrene block copolymer used below was purchased from Dongguan Mousheng Engineering Plastics Co., Ltd., model 503T.
[0031] Example 1 A thermoplastic elastomer composite polypropylene resin composition, whose raw materials include: 100g of polypropylene, 10g of styrene and butadiene block copolymer, 0.1g of dicyclohexyl terephthalamide, 3g of scratch resistance enhancer, 1g of nano silicon dioxide, 1g of antioxidant 1010, 0.1g of stearic acid monoglyceride, 1g of disteadecyl pentaerythritol diphosphite, 5g of dimethyl hydroxy silicone oil, 1g of nano graphene oxide and 5g of nano hydroxyapatite.
[0032] The scratch resistance enhancer was prepared by the following specific operation: 2 g of carboxyl polysiloxane with a molecular weight of 80,000 was added to 30 g of ethyl acetate, stirred at a speed of 50 r / min for 10 min, 1 g of amino-terminated polyamidoamine was added thereto, ultrasonic treatment was performed for 10 min at an ultrasonic frequency of 5 kHz, 0.1 g of N-hydroxysuccinimide and 0.01 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide were added, stirred at a temperature of 80°C for 1 h, ethyl acetate was removed by reduced pressure distillation, washed once with ethanol, and vacuum dried.
[0033] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 30°C for 1 min at a stirring speed of 500 r / min, add nano-hydroxyapatite and continue stirring for 1 h, perform ultrasonic treatment for 1 h at an ultrasonic frequency of 10 kHz, and obtain pretreated silicone oil; S2. Add polypropylene, styrene and butadiene block copolymer, dicyclohexyl terephthalamide, pretreated silicone oil, scratch resistance enhancer, nano silica, antioxidant 1010, stearic acid monoglyceride, and dioctadecyl pentaerythritol diphosphite into a twin-screw extruder for melting. The melting temperature is 185°C, the aspect ratio of the twin-screw extruder is 20:1, and extrusion granulation is performed.
[0034] Example 2 A thermoplastic elastomer composite polypropylene resin composition, the raw materials of which include: 150g of polypropylene, 30g of styrene and isoprene block copolymer, 1g of dicyclohexyl terephthalamide, 9g of scratch resistance enhancer, 5g of nano silicon dioxide, 3g of antioxidant 168, 1g of pentaerythritol stearate, 2g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, 10g of dimethyl hydroxy silicone oil, 5g of nano graphene oxide and 10g of nano hydroxyapatite.
[0035] The scratch resistance enhancer was prepared by the following specific operation: 6 g of carboxyl polysiloxane with a molecular weight of 100,000 was added to 50 g of ethyl acetate, stirred at a speed of 500 r / min for 30 min, 2 g of amino-terminated polyamidoamine was added thereto, ultrasonic treatment was performed for 20 min, the ultrasonic frequency was 15 kHz, 1 g of N-hydroxysuccinimide and 0.1 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide were added, stirred at a temperature of 90°C for 4 h, ethyl acetate was removed by reduced pressure distillation, washed with ethanol three times, and vacuum dried.
[0036] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 50°C for 3 min at a stirring speed of 1500 r / min, add nano-hydroxyapatite and continue stirring for 2 h, perform ultrasonic treatment for 2 h at an ultrasonic frequency of 20 kHz, and obtain pretreated silicone oil; S2. Add polypropylene, styrene and isoprene block copolymer, dicyclohexyl terephthalamide, pretreated silicone oil, scratch resistance enhancer, nano-silica, antioxidant 168, pentaerythritol stearate, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine into a twin-screw extruder for melting. The melting temperature is 210°C, the aspect ratio of the twin-screw extruder is 25:1, and extrusion granulation is performed.
[0037] Example 3 A thermoplastic elastomer composite polypropylene resin composition, the raw materials of which include: 110g of polypropylene, 25g of hydrogenated styrene-butadiene-styrene block copolymer, 0.3g of N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, 8g of scratch resistance enhancer, 2g of nano silicon dioxide, 2.5g of antioxidant 1010, 0.2g of oleic acid amide, 1.7g of dioctadecyl pentaerythritol diphosphite, 7g of dimethyl hydroxy silicone oil, 4g of nano graphene oxide and 7g of nano hydroxyapatite.
[0038] The scratch resistance enhancer was prepared by the following specific operation: 5 g of carboxyl polysiloxane with a molecular weight of 85,000 was added to 45 g of ethyl acetate, stirred at a speed of 100 r / min for 25 min, 1.3 g of amino-terminated polyamidoamine was added thereto, ultrasonic treatment was performed for 18 min, the ultrasonic frequency was 8 kHz, 0.7 g of N-hydroxysuccinimide and 0.01 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide were added, stirred at a temperature of 88°C for 2 h, ethyl acetate was removed by reduced pressure distillation, washed twice with ethanol, and vacuum dried.
[0039] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 45°C for 1.5 min at a stirring speed of 1200 r / min, add nano-hydroxyapatite thereto and continue stirring for 80 min, perform ultrasonic treatment for 100 min at an ultrasonic frequency of 12 kHz, and obtain pretreated silicone oil; S2. Add polypropylene, hydrogenated styrene-butadiene-styrene block copolymer, N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, pretreated silicone oil, scratch resistance enhancer, nano silica, antioxidant 1010, oleic acid amide, and dioctadecyl pentaerythritol diphosphite into a twin-screw extruder for melting. The melting temperature is 200°C, the aspect ratio of the twin-screw extruder is 21:1, and extrusion granulation is performed.
[0040] Example 4 A thermoplastic elastomer composite polypropylene resin composition, whose raw materials include: 130g of polypropylene, 15g of hydrogenated styrene-butadiene-styrene block copolymer, 0.7g of N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, 4g of scratch resistance enhancer, 4g of nano silicon dioxide, 1.5g of antioxidant 168, 0.8g of erucic acid amide, 1.3g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, 9g of dimethyl hydroxy silicone oil, 2g of nano graphene oxide and 9g of nano hydroxyapatite.
[0041] The scratch resistance enhancer was prepared by the following specific operation: 3 g of carboxyl polysiloxane with a molecular weight of 95,000 was added to 35 g of ethyl acetate, stirred at a speed of 400 r / min for 15 min, 1.7 g of amino-terminated polyamidoamine was added thereto, ultrasonic treatment was performed for 12 min, the ultrasonic frequency was 12 kHz, 0.3 g of N-hydroxysuccinimide and 0.05 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide were added, stirred at a temperature of 82°C for 3 h, ethyl acetate was removed by reduced pressure distillation, washed twice with ethanol, and vacuum dried.
[0042] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 35°C for 2.5 min at a stirring speed of 800 r / min, add nano-hydroxyapatite thereto and continue stirring for 100 min, perform ultrasonic treatment for 80 min at an ultrasonic frequency of 18 kHz, and obtain pretreated silicone oil; S2. Add polypropylene, hydrogenated styrene-butadiene-styrene block copolymer, N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, pretreated silicone oil, scratch resistance enhancer, nano silica, antioxidant 168, erucic acid amide, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine into a twin-screw extruder for melting. The melting temperature is 190°C, the aspect ratio of the twin-screw extruder is 23:1, and extrusion granulation is performed.
[0043] Example 5 A thermoplastic elastomer composite polypropylene resin composition, the raw materials of which include: 120g of polypropylene, 20g of hydrogenated styrene-butadiene-styrene block copolymer, 0.5g of N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, 6g of scratch resistance enhancer, 3g of nano silicon dioxide, 2g of antioxidant 1010, 0.5g of ethylene bisstearic acid amide, 1.5g of dioctadecyl pentaerythritol diphosphite, 8g of dimethyl hydroxy silicone oil, 3g of nano graphene oxide and 8g of nano hydroxyapatite.
[0044] The scratch resistance enhancer was prepared by the following specific operation: 4 g of carboxyl polysiloxane with a molecular weight of 90,000 was added to 40 g of ethyl acetate, stirred at a speed of 300 r / min for 20 min, 1.5 g of amino-terminated polyamidoamine was added thereto, ultrasonic treatment was performed for 15 min, the ultrasonic frequency was 10 kHz, 0.5 g of N-hydroxysuccinimide and 0.03 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide were added, stirred at a temperature of 85°C for 2.5 h, ethyl acetate was removed by reduced pressure distillation, washed twice with ethanol, and vacuum dried.
[0045] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 40°C for 2 min at a stirring speed of 1000 r / min, add nano-hydroxyapatite thereto and continue stirring for 90 min, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 15 kHz, and obtain pretreated silicone oil; S2. Add polypropylene, hydrogenated styrene-butadiene-styrene block copolymer, N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, pretreated silicone oil, scratch resistance enhancer, nano silica, antioxidant 1010, ethylene bisstearamide, and dioctadecyl pentaerythritol diphosphite into a twin-screw extruder for melting. The melting temperature is 195°C, the aspect ratio of the twin-screw extruder is 22:1, and extrusion granulation is performed.
[0046] Comparative Example 1 A thermoplastic elastomer composite polypropylene resin composition, the raw materials of which include: 120g of polypropylene, 20g of hydrogenated styrene-butadiene-styrene block copolymer, 0.5g of N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, 6g of scratch resistance enhancer, 3g of nano silicon dioxide, 2g of antioxidant 1010, 0.5g of ethylene bisstearic acid amide, 1.5g of dioctadecyl pentaerythritol diphosphite, 8g of dimethyl hydroxy silicone oil, 3g of nano graphene oxide and 8g of nano hydroxyapatite.
[0047] The scratch resistance enhancer was prepared by the following specific operation: 4 g of carboxyl polysiloxane with a molecular weight of 90,000 was added to 40 g of ethyl acetate, stirred at a speed of 300 r / min for 20 min, 1.5 g of amino-terminated polyamidoamine was added thereto, ultrasonic treatment was performed for 15 min, the ultrasonic frequency was 10 kHz, 0.5 g of N-hydroxysuccinimide and 0.03 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide were added, stirred at a temperature of 85°C for 2.5 h, ethyl acetate was removed by reduced pressure distillation, washed twice with ethanol, and vacuum dried.
[0048] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1, adding nano-hydroxyapatite to dimethyl hydroxy silicone oil, stirring for 90 minutes, and ultrasonic treatment for 90 minutes at an ultrasonic frequency of 15 kHz to obtain pretreated silicone oil; S2. Add polypropylene, hydrogenated styrene-butadiene-styrene block copolymer, N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, pretreated silicone oil, nano-graphene oxide, scratch resistance enhancer, nano-silica, antioxidant 1010, ethylene bisstearamide, and dioctadecyl pentaerythritol diphosphite into a twin-screw extruder for melting. The melting temperature is 195°C, the aspect ratio of the twin-screw extruder is 22:1, and extrusion granulation is performed.
[0049] Comparative Example 2 A thermoplastic elastomer composite polypropylene resin composition, the raw materials of which include: 120g of polypropylene, 20g of hydrogenated styrene-butadiene-styrene block copolymer, 0.5g of N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, 6g of scratch resistance enhancer, 3g of nano silicon dioxide, 2g of antioxidant 1010, 0.5g of ethylene bisstearic acid amide, 1.5g of dioctadecyl pentaerythritol diphosphite, 8g of dimethyl hydroxy silicone oil, 3g of nano graphene oxide, 8g of nano hydroxyapatite, 4g of carboxyl polysiloxane with a molecular weight of 90,000, and 1.5g of amino-terminated polyamidoamine.
[0050] The preparation method of the thermoplastic elastomer composite polypropylene resin composition comprises the following steps: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 40°C for 2 min at a stirring speed of 1000 r / min, add nano-hydroxyapatite thereto and continue stirring for 90 min, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 15 kHz, and obtain pretreated silicone oil; S2. Add polypropylene, hydrogenated styrene-butadiene-styrene block copolymer, N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, pretreated silicone oil, carboxyl polysiloxane, amino-terminated polyamide amine, nano silica, antioxidant 1010, ethylene bisstearamide, and dioctadecyl pentaerythritol diphosphite into a twin-screw extruder for melting. The melting temperature is 195°C, the aspect ratio of the twin-screw extruder is 22:1, and extrusion granulation is performed.
[0051] The thermoplastic elastomer composite polypropylene resin compositions obtained in Example 5 and Comparative Examples 1-2 were respectively added to an injection molding machine for injection molding at a temperature of 200° C., an injection pressure of 30 MPa, a holding time of 50 s, and a cooling time of 20 s to obtain injection molded samples.
[0052] The flexural modulus of the above-mentioned groups of samples was measured with reference to GB / T 9341-2008 "Determination of flexural properties of plastics". The impact strength of the above-mentioned groups of samples was measured with reference to GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test". The tensile strength and elongation at break of the above-mentioned groups of samples were measured with reference to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics".
[0053] like Figure 1 and Figure 2 As shown, the bending modulus, impact strength, tensile strength and elongation at break of the samples in Example 5 are the highest, which are better than those in Comparative Examples 1-2 (P < 0.05).
[0054] The scratch resistance of each group of samples was tested using the PV3952 Volkswagen scratch resistance test, and dL was used to characterize the scratch resistance (immediate test).
[0055] like Figure 3 As shown, the dL value of the sample in Example 5 is smaller than that in Comparative Examples 1-2, but there is no significant difference (P>0.05), indicating that the scratch resistance of the three groups of samples is good.
[0056] The scratch self-repairing performance was tested by injection molding the thermoplastic elastomer composite polypropylene resin composition obtained in Example 5 and Comparative Examples 1-2 into leather grain samples, with a scratch force of 10N, an automatic repair temperature of 45±2°C, and a time of 30min. The whiteness change value (△L) was used for characterization. If automatic repair occurs after scratching, △L becomes smaller.
[0057] △L = whiteness value of a sample after a certain period of time after scratching - whiteness value of the sample before scratching like Figure 4 As shown, the △L of the three groups of samples decreases with time, indicating that the three groups of samples undergo automatic repair. As soon as the three groups of samples are scratched, the △L of the Example 5 group is the smallest, which is better than the Comparative Examples 1-2 groups (P < 0.05), indicating that the Example 5 group of samples is more scratch-resistant. At the same time, the △L of the Example 5 group of samples is always the smallest, which is better than the Comparative Examples 1-2 groups (P < 0.05), proving that the Example 5 group of samples is not only scratch-resistant, but also has better self-repair ability.
[0058] The applicant believes that this is because the present invention combines a lamellar graphene structure on the organic silicon macromolecular chain of dimethylhydroxy silicone oil, and then further forms a stable hydrogen bond structure with the hydroxyl group on the nanohydroxyapatite. Since graphene oxide is a honeycomb structure at the microscopic level, it is combined with the organic silicon macromolecular chain, so that the dispersion uniformity in the base material composed of polypropylene and styrene thermoplastic elastomer is extremely high, which promotes the excellent bending modulus and impact resistance of the resulting composition, and its stable lamellar structure can effectively protect the interface and enhance the impact toughness of the material. Even if the material is damaged, the organic silicon macromolecular chain cooperates with the nanohydroxyapatite to repair and combine again through hydrogen bonds. The present invention uses carboxyl polysiloxane as the main chain, and combines it with amino-terminated polyamide amine. By controlling the ratio of the two, and then controlling the degree of grafting on the polysiloxane main chain, the resulting scratch resistance enhancer has a similar main chain structure to the pretreated silicone oil, and the molecular chain structures are entangled with each other. It has been confirmed through experiments that the present invention exhibits reversible thermoplasticity when heat treated at 40-50°C, and utilizes multiple hydrogen bonds therein to achieve reversible physical crosslinking, forming hydrogen bonds as physical crosslinking points, which can give the interface excellent repair performance. In the scratch-resistant enhancer, since a large number of dendritic polyamide amine structures are combined on the siloxane molecular chains and dispersed in the continuous phase polypropylene, when subjected to external forces, its dendritic structures are similar to anchoring structures combined with polypropylene, which can not only quickly disperse the external forces through the entangled siloxane molecular chains, but also make the surface structure not easy to break, and the impact resistance is further enhanced.
[0059] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A thermoplastic elastomer composite polypropylene resin composition, characterized in that: The raw materials include, by mass, 100-150 parts of polypropylene, 10-30 parts of styrene-based thermoplastic elastomer, 0.1-1 parts of nucleating agent, 3-9 parts of scratch resistance enhancer, 1-5 parts of nano silicon dioxide, 1-3 parts of antioxidant, 0.1-1 parts of lubricant, 1-2 parts of heat stabilizer, 5-10 parts of dimethyl hydroxy silicone oil, 1-5 parts of nano graphene oxide and 5-10 parts of nano hydroxyapatite.
2. The thermoplastic elastomer-composite polypropylene resin composition according to claim 1, characterized in that: The melt flow rate of polypropylene is 15-20 g / 10 min at 230°C and a load of 2.16 kg.
3. The thermoplastic elastomer-composite polypropylene resin composition according to claim 1, characterized in that: The styrene-based thermoplastic elastomer is at least one of a styrene-butadiene block copolymer, a styrene-isoprene block copolymer, and a hydrogenated styrene-butadiene-styrene block copolymer.
4. The thermoplastic elastomer-composite polypropylene resin composition according to claim 1, characterized in that: The nucleating agent is dicyclohexyl terephthalamide or N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide.
5. The thermoplastic elastomer-composite polypropylene resin composition according to claim 1, characterized in that: The scratch resistance enhancer is prepared by the following specific operation: adding carboxyl polysiloxane to ethyl acetate and stirring for 10-30 minutes, adding amino-terminated polyamidoamine thereto, ultrasonically treating for 10-20 minutes, adding N-hydroxysuccinimide and a catalyst, stirring at 80-90° C. for 1-4 hours, removing ethyl acetate by reduced pressure distillation, washing, and vacuum drying.
6. The thermoplastic elastomer-composite polypropylene resin composition according to claim 5, characterized in that: The mass ratio of carboxyl polysiloxane, amino-terminated polyamidoamine, N-hydroxysuccinimide and catalyst is 2-6:1-2:0.1-1:0.001-0.
1.
7. The thermoplastic elastomer-composite polypropylene resin composition according to claim 1, characterized in that: The antioxidant is antioxidant 1010 and / or antioxidant 168.
8. The thermoplastic elastomer-composite polypropylene resin composition according to claim 1, characterized in that: The heat stabilizer is at least one of an amine heat stabilizer and a phosphite heat stabilizer.
9. The thermoplastic elastomer-composite polypropylene resin composition according to claim 1, characterized in that: The lubricant is at least one of a stearic acid complex ester lubricant and an amide lubricant.
10. A method for preparing the thermoplastic elastomer-polypropylene resin composition according to any one of claims 1 to 9, characterized in that: The steps include: S1. Add nano-graphene oxide to dimethyl hydroxy silicone oil, stir at 30-50° C. for 1-3 min, add nano-hydroxyapatite thereto, continue stirring for 1-2 h, and perform ultrasonic treatment to obtain pretreated silicone oil; S2, mixing polypropylene, styrene-based thermoplastic elastomer, nucleating agent, pre-treated silicone oil, scratch resistance enhancer, nano silicon dioxide, antioxidant, lubricant, and heat stabilizer, melt-extruding, and granulating.
Citation Information
Patent Citations
Polypropylene thermoplastic elastomer with scratch self-repairing function and preparation method thereof
CN102516668A
Preparation method and application of graphene oxide-polyurethane foam material
CN103408718A
Cited By
High-performance polypropylene plastic woven bag and production method
CN120025630A